2014
DOI: 10.1002/mrc.4130
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR spectra of alcohols and diols in chloroform: DFT/GIAO calculation of chemical shifts

Abstract: Proton nuclear magnetic resonance (NMR) shifts of aliphatic alcohols in chloroform have been computed on the basis of density functional theory, the solvent being included by the integral-equation-formalism polarisable continuum model of Gaussian 09. Relative energies of all conformers are calculated at the Perdew, Burke and Ernzerhof (PBE)0/6-311+G(d,p) level, and NMR shifts by the gauge-including atomic orbital method with the PBE0/6-311+G(d,p) geometry and the cc-pVTZ basis set. The 208 computed CH proton N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 65 publications
2
10
0
Order By: Relevance
“…Likewise, at low temperature (À193 C) Pekh et al observed only one chair conformer in dichloromethane [16].With the assumption that all three OH rotamers of the dominant conformer are populated, we calculated the trans, g þ and g e rotamers of the OH eq chair of (þ)-menthol with the isopropyl group in the g þ position (Table 1). In agreement of our analysis, Lomas [32] investigated (À)-menthol and found the g e rotamer of the isopropyl group as dominant conformer, with the crystal structure revealing the isopropyl group in the gauche position [7]. However, pure computational results differ even between similar levels of theory (Table 2).…”
Section: (þ)-(1s3s4r)-mentholsupporting
confidence: 80%
“…Likewise, at low temperature (À193 C) Pekh et al observed only one chair conformer in dichloromethane [16].With the assumption that all three OH rotamers of the dominant conformer are populated, we calculated the trans, g þ and g e rotamers of the OH eq chair of (þ)-menthol with the isopropyl group in the g þ position (Table 1). In agreement of our analysis, Lomas [32] investigated (À)-menthol and found the g e rotamer of the isopropyl group as dominant conformer, with the crystal structure revealing the isopropyl group in the gauche position [7]. However, pure computational results differ even between similar levels of theory (Table 2).…”
Section: (þ)-(1s3s4r)-mentholsupporting
confidence: 80%
“…Additionally, calculations for HCO 3 , CO 3 , CH 3 COO, and HCOO radicals were performed employing the Gaussian 09 computational software package [34]. B3LYP functional in combination with the 6-311 + G (2d, p) basis set were used [35][36][37].…”
Section: Computational Detailsmentioning
confidence: 99%
“…The three-dimensional structure (3D) of chlorpyrifos was downloaded from the ChemSpider database and the B3LYP/6-31G** level was used with Gaussian 09 (Lomas, 2014;Premkumar et al, 2015). Figure 2(b) and (c) shows the HOMO and LUMO orbits of chlorpyrifos using the Multiwfn program (Lu & Chen, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The initial model of the chlorpyrifos was extracted from the ChemSpider database. Geometric optimization of the chlorpyrifos was conducted at the B3LYP/6-31G** level using Gaussian 09 (Lomas, 2014;Premkumar, Jawahar, Mathavan, Kumara Dhas, & Milton Franklin Benial, 2015).…”
Section: System Preparationmentioning
confidence: 99%
See 1 more Smart Citation